(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
In this paper, the authors presented the characteristic cases from the case law of the European Court of Human Rights in which members of the Islamic community considered that their freedom of religion under Article 9 of the European Convention on Human Rights and Fundamental Freedoms has been violated. At the same time, in those cases, there was frequently violation of Article 2 of Protocol No. 1 to the Convention, which provides for the right to education, cumulatively with above mention article. The starting point is the case of Dahlab v. Switzerland, after which the authors specifically addressed several other cases in which the European Court of Human Rights considered these rights.